Quality Control and Chronology: Response to Inomata and Colleagues. Issue 1 (27th March 2019) - Love, Michael
Abstract : I thank my colleagues for their comments, but I disagree with their assessment. Abstract : Agradezco a mis colegas por sus comentarios, pero estoy en desacuerdo con su evaluación.